The Role of History Learning in Cultivating Nationalism Attitudes of Class XI Social Sciences Students of SMA Negeri 1 Pecangaan - Amelia, Citra Ayu (Universitas Negeri Semarang, 2018)
This study aims to: (1) Describe the implementation of the teaching of history in planting nationalism among students of class XI Social Science at Pecangaan Senior High School. This includes examining the curriculum, teaching strategies, and educational activities teachers employ to instill a sense of national pride and awareness in students. (2) Describe the attitude of nationalism among class XI Social Science students at Pecangaan Senior High School. This involves assessing students' perceptions, behaviors, and expressions of nationalism within and outside the classroom. (3) Identify teachers' constraints in planting nationalism through history teaching in class XI Social Science at Pecangaan Senior High School. These constraints may include challenges such as limited resources, varying levels of student engagement, and external socio-political factors. (4) Describe the efforts of teachers to overcome these constraints in teaching history to promote nationalism among students in class XI Social Science at Pecangaan Senior High School. This includes innovative teaching methods, extracurricular activities, and collaborations with other educational institutions or community organizations. The research method employed in this study is qualitative. This approach is chosen to gain an in-depth understanding of the processes, challenges, and outcomes of teaching history to foster nationalism. Data collection methods may include interviews with teachers and students, classroom observations, and analysis of educational materials and student work. Through qualitative analysis, the study aims to provide a comprehensive overview of the current state of history education related to nationalism at Pecangaan Senior High School and offer insights for potential improvements.